2007
DOI: 10.1160/th07-03-0225
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2 expressing circulating (progenitor) cell populations in volunteers and cancer patients

Abstract: Circulating cells of several lineages are thought to participate in angiogenesis and tumor growth. Experimental studies in tumor-bearing mice have pointed to the potential importance of VEGF-responding circulating (endothelial) progenitor cells in tumor growth. We have studied circulating CD31- and/or CD34-positive cell populations with a low to moderate VEGFR2 expression in human volunteers and cancer patients. We recognized four cell populations, which were further characterized by their content of major hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…The cutoff value for CD133 positivity in HPCs was determined based on isotype control and was adjusted for every individual sample. CECs are CD34 bright , which are almost uniformly positive for VEGFR2, but lack both markers CD45 and CD133 as previously defined (Vroling et al, 2007(Vroling et al, , 2009 (Figure 1). …”
Section: Definitions Of Hpcs and Cecs Populationssupporting
confidence: 75%
See 1 more Smart Citation
“…The cutoff value for CD133 positivity in HPCs was determined based on isotype control and was adjusted for every individual sample. CECs are CD34 bright , which are almost uniformly positive for VEGFR2, but lack both markers CD45 and CD133 as previously defined (Vroling et al, 2007(Vroling et al, , 2009 (Figure 1). …”
Section: Definitions Of Hpcs and Cecs Populationssupporting
confidence: 75%
“…Blood from SO/ER-treated patients was collected in EDTA tubes and the circulating HPCs and CECs were measured using a fullblood flow cytometric method as previously described (Vroling et al, 2007(Vroling et al, , 2009. (CD133 þ ) HPCs were defined as CD34 bright / CD45 dim (and CD133 þ ) and CECs were defined as CD34 bright / CD45 neg and largely positive for VEGFR2.…”
Section: Evaluation Of Cells and Plasma Biomarkersmentioning
confidence: 99%
“…These data suggest a possible marker (e.g., VEGFR2+ macrophages or circulating monocytes) for identifying pancreatic cancer and a possible marker for the efficacy of antiangiogenic treatment. It is worth noting that higher levels of circulating VEGFR2+ monocytes/macrophages have recently been identified in patients with various advanced solid tumors compared with healthy volunteers (36). The inductive factor in human patients has not been elucidated; however, we show that the cytokine PTN is sufficient to induce VEGFR2 expression in macrophages, a function of PTN that is relevant to the progression of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 55%
“…41). These findings have raised considerable questioning of the reliability of the flow cytometry method for CEC measurement (38,42,43). Recently, in 2007, Strijbos et al argued that cells identified as CECs by flow cytometry in these studies were, in fact, large platelets (42).…”
Section: Aadmentioning
confidence: 99%